A preference analysis of renewable energy alternatives in Malaysia using fuzzy VIKOR method - Jamilah Mohd Shariff,; Daud Mohamad,; Shahirah Amin,; Nur Farha Baha, (Penerbit Universiti Kebangsaan Malaysia, 2020)
In Malaysia, the main consumed energy is the fossil fuel. As the population continues to increase and the fossil fuels begin to deplete rapidly, it may not be possible to depend solely on fossil fuel. A feasible alternative should be sought to replace the dependency of the fossil fuel. In this paper, an evaluation is made on the experts’ preference of the type of eco-friendly renewable energy that is suitable to be used in Malaysia between biomass, solar, hydro or hybrid energy using the fuzzy VIKOR method. Since the evaluation considers subjective element that involves human perceptions and knowledge experts, the Fuzzy VIKOR method is considered to be an appropriate choice. The Fuzzy VIKOR method has the ability to deal with multi-conflicting or non-commensurable criteria in the ranking and selecting the alternatives. The evaluation is based on four main criteria which are Efficiency, Operation, Land Use and Job Creation of each alternative. It is found that the main concern of the renewable energy choice is on its efficiency and the hydro energy is the most preferred alternative energy to be used in Malaysia.